Evaluation of Some Organic Extracts in in Vitro to Control Fusarium Solani Causing Chilli Wilt - M.G YELMAME,; B.P. MEHTA,; A.J.DESHMUKH,; V.A.PATIL, (International Journal of Pharma and Bio Sciences, 2010)
Investigation on wilt (F. solani) of chilli (C.frutescens L.) under south Gujarat conditions was carried out in Dept, of Plant Pathology Lab., N. M. College of Agriculture, NAU, Navsari in 2004 to find out suitable management strategies. It is difficult to control F. solani as it is having soil inhabiting nature. This led to trials on the use of organics to control the pathogen. The extracts of different organics of neem cake, mustard cake, FYM, groundnut cake, poultry manure, press mud, castor cake and coconut cake were tested against F. solani by poisoned food technique in in vitro. Least growth of the pathogen was recorded in the extracts of neem cake showing excellent inhibitory effect i.e 59.8 % against F. solani. Next best in order of merit was mustard cake (52.61 %) followed by FYM (49.40 %), groundnut cake (44.80 %), poultry manure (42.29 %), and least by other cakes.